The potential of solar industrial process heat applications - Kalogirou, Soteris A. (My University, 2003)
The temperature requirements of solar industrial process heat applications range from 60 °C to 260 °C. The characteristics of medium to medium-high temperature solar collectors are given and an overview of efficiency and cost of existing technologies is presented. Five collector types have been considered in this study varying from the simple stationary flat-plate to movable parabolic trough ones. Based on TRNSYS simulations, an estimation of the system efficiency of solar process heat plants operating in the Mediterranean climate are given for the different collector technologies. The annual energy gains of such systems are from 550 to 1100 kWh/m2 a. The resulting energy costs obtained for solar heat are from 0.015 to 0.028 C£/kWh depending on the collector type applied. The viabilities of the systems depend on their initial cost and the fuel price. None of these costs however is stable but change continuously depending on international market trends and oil production rates. The costs will turn out to be more favourable when the solar collectors become cheaper and subsidisation of fuel is removed. Therefore the optimisation procedure suggested in this paper should be followed in order to select the most appropriate system in each case.
Keywords: Industrial process heat; Solar collectors; Economics; Life cycle savings